Cybersecurity Policy and Its Implementation in Indonesia (Law Research Review Quarterly, 2021)
The aim of national defense is to protect and save the integrity of the Unitary State of the Republic of Indonesia, the sovereignty of the state, and its security from all kinds of threats, both military and non-military. One of the non-military threats that could potentially threaten the sovereignty and security of the nation-state is the misuse of technology and information in cyberspace. This paper is intended to analyze the cybersecurity policy in Indonesia and its challenges. This paper highlighted that the threat of irresponsible cyber attacks can be initiated by state and non-state actors. The actor may be an individual, a group of people, a faction, an organization, or even a country. Therefore, the government needs to anticipate cyber threats by formulating a cyber security strategy and determining comprehensive steps to defend against cyber attacks; type and scale of retaliation, and drafting the rule of law.